Inconsistencies in the execution of death sentence / Rubiah Jaffar - Jaffar, Rubiah (Faculty of Law, 1985)
Administration of criminal justice in Malaysia in governed by the Criminal Procedure Code (F.M.S. Cap 6). Section 15 of the said code briefly explained how arrest are made. If such person forcibly resist endeavour to arrest him or attempt to evade the arrest such Officer or other person may use all means necessary to effect the arrest. The section does not give the right to cause the death of a person who is not accused of an offence punishable with death or with imprisonment for life.